Power Quality Evaluation of a High-Power Residential Load: An Experimental - Bozkurt, Altug; Yuzer, Ersan Omer (GAZI UNIV, 2026)
The global energy demand is increasing day by day due to factors such as industrialization, technological advancements, and population growth. In order to meet this growing demand, merely exploring new energy sources is not sufficient; issues such as energy efficiency and power quality are also gaining increasing importance. Harmonics, one of the most critical parameters of power quality, refer to the distortions caused by electrical devices in power systems and can directly affect the efficiency and safety of energy systems. Household appliances such as air conditioners, computers, televisions, washing machines, and dishwashers are among the major contributors to harmonic pollution. In this study, the harmonic effects of three different washing machines manufactured in different years were examined. The primary objective of this study is to analyze the impact of washing machines on power quality at different washing temperatures and to compare their harmonic generation levels. Within the scope of the study, harmonics generated during washing cycles at different temperatures (30 degrees C, 60 degrees C, and 90 degrees C) were analyzed in detail for each washing machine. Measurements were conducted using a Fluke 435 power quality analyzer, and the obtained data were processed using MATLAB software for detailed analysis. The measurements revealed that the harmonic levels of washing machines vary depending on the model year, motor type, and washing temperature. It was observed that older models produced lower harmonic levels, whereas modern inverter motor washing machines exhibited higher harmonic levels. Additionally, it was determined that harmonic distortion changes as the washing temperature increases. The results highlight the significance of design modifications aimed at reducing the harmonic generation of electrical household appliances and the importance of techniques that enhance energy efficiency. This study aims to contribute to raising awareness among consumers and engineers regarding power quality and harmonic management, thereby guiding the development of more efficient and environmentally friendly electrical devices.
Keywords: Residential load; washing machine; harmonic evaluation; non-linear loads; power quality; Engineering